Revisitando o regionalismo como fundamento da questão regional - Iná Elias de Castro (Confins)
The proposal in this paper is to recover the discussions on regionalism taking as a starting point that every idea of regionalism is based on a regional delimitation, which in the case of the old regionalism is grounded in the well elaborated idea of a regional issue and that there is no consensus about the meaning and functionality of the concept. Briefly, two axes are taken around which the discussions and controversies about regionalism as a problem are based today: the “old” and the “new” regionalism. In these axes will be retaken: the discussion of the conditions necessary for regionalism as a concept and as action strategy, and the investigation of its current characteristics in view of the possibilities of new social, political and economic issues that are imposed on subnational and supranational scales. While the idea of the old regionalism is nourished from the perspective of the region as an issue, that is, as a spatial continent of a problem or even conflicts of a cultural, political or economic order at the subnational scale; instead the new regionalism presents for the region's debate as a spatial extension of innovations and economic potential, also on a supranational scale. The aim of this paper is to discuss regionalism as a problem at different scales and situations. The text is divided into two parts: in the first, I return to the debate on what today can be called old regionalism and some points around the discussion about its foundations and justifications. The second part presents the characteristics and the debate on the so-called new regionalism.